Bonded to the abuser : how victims make sense of childhood abuse - Baker, Amy J. L.; Schneiderman, Mel (Lanham, Maryland : Rowman & Littlefield, 2015)
"Tens of thousands of children are removed from home each year due to some form of child maltreatment, usually physical neglect, physical abuse, or sexual abuse, although sometimes for emotional abuse as well. An additional significant number of children are victims of child maltreatment but remain in their home. Extensive research reveals the far reaching and long lasting negative impact of maltreatment on child victims, including on their physical, social, emotional, and behavioral functioning. One particularly troubling and complicated aspect is how the child victim forms (and maintains) a 'traumatic bond' with his abuser, even becoming protective and defensive of that person despite the pain and suffering they have caused. This book will provide the reader with the essential experience of understanding how children make meaning of being maltreated by a parent, and how these traumatic bonds form and last. Through an examination of published memoirs of abuse, the authors analyze and reveal the commonalities in the stories to uncover the ways in which adult victims of childhood abuse understand and digest the traumatic experiences of their childhoods. This understanding can inform interventions and treatments designed for this vulnerable population and can help family and friends of victims understand more fully the maltreatment experience 'from the inside out'"--Amazon.com.
Stories of physical abuse -- Making meaning of physical abuse -- Stories of sexual abuse -- Making meaning of sexual abuse -- Stories of emotional abuse -- Making meaning of emotional abuse -- Stories of emotional neglect -- Making meaning of emotional neglect -- Stories of physical neglect -- Making meaning of physical neglect -- Moving forward.
Includes bibliographical references and index.
Text in English.
Keywords: Adult child abuse victims -- Case studies; Adult child abuse victims -- Rehabilitation